How to modify 7-azaindole to form cytotoxic Pt(II) complexes: highly in vitro anticancer effective cisplatin derivatives involving halogeno-substituted 7-azaindole - Štarha, Pavel; Trávníček, Zdeněk; Popa, Alexandr; Popa, Igor; Muchová, Tereza; Brabec, Viktor (Journal of inorganic biochemistry, 2012)
The platinum(II) dichlorido and oxalato complexes of the general formula cis-[PtCl(2)(nHaza)(2)] (1-3) [Pt(ox)(nHaza)(2)] (4-6) involving 7-azaindole halogeno-derivatives (nHaza) were prepared and thoroughly characterized. A single-crystal X-ray analysis of cis-[PtCl(2)(3ClHaza)(2)]·DMF (1·DMF; 3ClHaza symbolizes 3-chloro-7-azaindole) revealed a distorted square-planar arrangement with both the 3ClHaza molecules coordinated through their N7 atoms in a cis fashion. In vitro cytotoxicity of the complexes was evaluated by an MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay against the HOS (osteosarcoma), MCF7 (breast adenocarcinoma) and LNCaP (prostate adenocarcinoma) human cancer cell lines. The dichlorido complexes 1-3 (IC(50)=3.8, 3.9, and 2.5 μM, respectively) showed significantly higher in vitro anticancer effect against HOS as compared with cisplatin, whose IC(50)=37.7 μM. The biological effect of cisplatin against MCF7 (IC(50)=24.5 μM) and LNCaP (IC(50)=3.8 μM) was also exceeded by 1-3 (except for 2 against LNCaP), but the difference can be classified as significant only in the case of 1 (IC(50)=3.4 μM) and 3 (IC(50)=2.0 μM) against MCF7. The molecular pharmacological studies (RNA synthesis by T7 RNA polymerase in vitro) proved that 1-3 bind to DNA in a similar manner as cisplatin, since the RNA synthesis products of 1-3 and cisplatin showed a similar sequence profile of major bands.
Keywords: protinádorové látky; Neoplasms; Cell Line, Tumor; Drug Screening Assays, Antitumor; indoly; Cytotoxins; RNA nádorová; lidé; RNA; Humans; Indoles; screeningové testy protinádorových léčiv; cisplatina; nádory; nádorové buněčné linie; Cisplatin; RNA, Neoplasm; cytotoxiny; Antineoplastic Agents